Spominski predmeti - poskus opredelitve pojma in raziskovanja - Habinc, Mateja (Etnolog. Nova vrsta (Ljubljana), 2002)
The article first summarises a range of domestic and foreign authors in order to illustrate the variety of different names used to refer to objects which the author collectively calls "objects of memory". The article then considers some of their common properties and their use as aids and sources for research. The author indicates the possibility of treating objects of memory as objects, not merely as sources of a culture in this connection she discusses the research of how the objects depend on and are connected with theway of living of the individuals who selected them and preserved them for memory. The article concludes with an attempt at placing such research in thefield of the study of material culture which deals with the non-economic attributes of consumption.
Keywords: predmeti; materialna kultura; terminologija; terminology; raziskovanje; metode